You are my people an introduction to prophetic literature - Stulman, Louis 1953-; Kim, Hyun Chul Paul 1965- (Nashville Abingdon Press, 2010)
Illuminates how the prophetic voices of the Old Testament can still speak hope to exiled and disenfranchised people.
Description based on publisher supplied metadata and other sources
Keywords: Bibel; Electronic books